Understanding the time-course of an intervention’s mechanisms: a framework for improving experiments and evaluations - Linning, Shannon J. (Journal of experimental criminology, 2019)
The crime prevention evaluation literature has identified several potential side effects of interventions. These often-unintended consequences occur at different stages of prevention processes, including before official start dates. They can improve or reduce intervention impacts. Evaluations using before-and-after designs with or without controls can fail to identify these effects. We describe a longitudinal framework to guide the design and evaluation of interventions that can account for these side effects when causal mechanisms are better understood.